Transformation of Management Accounting in the Digital Era: Current Challenges and Opportunities - Yudi Zatnika; Iin Safariah (STIE AMKOP, 2023)
This research aims to investigate the impact of digital transformation on management accounting practices and its implications for organizations. The study seeks to understand how management accountants adapt to new technologies, the role of digital tools in decision-making, and the challenges faced by organizations during the digital transition. A literature review approach is employed to gather and synthesize existing research on digital transformation in management accounting. Peer-reviewed academic papers, industry reports, and relevant literature are analyzed to explore the challenges, opportunities, and best practices associated with the integration of digital technologies. The research reveals that digital transformation significantly enhances efficiency and accuracy in management accounting processes. Real-time reporting and data visualization empower organizations to make timely and informed decisions. The adoption of AI and data analytics enables predictive analysis, contributing to proactive decision-making. However, challenges such as skill adaptation, data management, and cybersecurity must be addressed to fully capitalize on the potential of digitalization. Organizations must foster a culture of continuous learning and embrace technology to remain competitive and successful in the digital era. Keywords: digital transformation, management accounting, digital technologies, decision-making, efficiency